Making a meal for a unicorn - Owen, Ruth, 1967- (Minneapolis, Minnesota : Bearport Publishing Company, 2022)
"How do you feed a hungry unicorn that has stopped by for dinner? Make a meal that's yummy for your unicorn guest (and pretty tasty for you, too)! Start with a carrot cake milkshake to serve your friend their favorite treat alongside an appetizer inspired by their famous horn. Then, feast on a rainbow veggie tart for the main course. When you're ready for dessert, whip up a batch of magical unicorn cupcakes. Yum! Don't forget to explore more about unicorn facts and fiction so you have plenty to talk about during your mythical meal"--
Includes bibliographical references and index.
Ages 7-10
Grades 2-3
Keywords: Cooking -- Juvenile literature; Unicorns -- Juvenile literature; Cookbooks